2020
DOI: 10.1111/acem.14053
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Home Pulse Oximetry Monitoring in COVID‐19 Patients Discharged From the Emergency Department Identifies Need for Hospitalization

Abstract: Objectives Our objective was to evaluate patient‐reported oxygen saturation (SpO2) using pulse oximetry as a home monitoring tool for patients with initially nonsevere COVID‐19 to identify need for hospitalization. Methods Patients were enrolled at the emergency department (ED) and outpatient testing centers. Each patient was given a home pulse oximeter and instructed to record their SpO2 every 8 hours. Patients were instructed to return to the ED for sustained home SpO2 < 92% or if they felt they needed emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
184
1
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(198 citation statements)
references
References 21 publications
(22 reference statements)
6
184
1
7
Order By: Relevance
“…Emerging international evidence has indicated that lower thresholds for oxygen saturation, are associated with worse patient outcomes 2 26 . In the case of our review, even though some authors argued that pulse oximetry identified the need for hospitalisation when using a cutoff of 92% 16 , we could not reach conclusions in relation to patient safety and the degree to which remote home monitoring models can conclusively identify cases of deterioration at an earlier stage in the disease trajectory. The main reasons were lack of standardised reporting across articles in relation to these outcome measures and how these were measured, as well as the limitation that none of the articles used comparators.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Emerging international evidence has indicated that lower thresholds for oxygen saturation, are associated with worse patient outcomes 2 26 . In the case of our review, even though some authors argued that pulse oximetry identified the need for hospitalisation when using a cutoff of 92% 16 , we could not reach conclusions in relation to patient safety and the degree to which remote home monitoring models can conclusively identify cases of deterioration at an earlier stage in the disease trajectory. The main reasons were lack of standardised reporting across articles in relation to these outcome measures and how these were measured, as well as the limitation that none of the articles used comparators.…”
Section: Discussioncontrasting
confidence: 59%
“…Medina et al 13 reported following up patients on the step-down pathway for 7 days post-discharge from hospital and those on the pre-admission pathway for 14 days. Shah et al 16 followed-up patients on their pre-admission pathway for 7 days. Hutchings et al 6 referred patients to their GP for follow-up after discharging them from the remote home monitoring pathway.…”
Section: Stages Of Remote Home Monitoringmentioning
confidence: 99%
“…This month's AEM article confirms the utility of home pulse oximetry monitoring as a screening tool for COVID‐19 pneumonia 6 . This study validates pulse oximetry for determining the need for hospitalization.…”
mentioning
confidence: 54%
“…Hopefully, such techniques will work even better if we identify pneumonia earlier with only mild hypoxia and before severe lung injury. This month's study by Shah et al 6 supports the growing body of literature that pulse oximetry monitoring should be a standard of care for discharging known or suspected COVID‐19 patients.…”
mentioning
confidence: 60%
“…We write to thank Shah et al 1 for sharing their article “Novel Use of Home Pulse Oximetry Monitoring in COVID‐19 Patients Discharged From the Emergency Department Identifies Need for Hospitalization” and provide an international perspective from Australia.…”
mentioning
confidence: 99%